The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1145/3375192
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Diversity of Facebook Reactions to Research

Abstract: Online and in the real world, communities are bonded together by emotional consensus around core issues. Emotional responses to scientific findings often play a pivotal role in these core issues. When there is too much diversity of opinion on topics of science, emotions flare up and give rise to conflict. This conflict threatens positive outcomes for research. Emotions have the power to shape how people process new information. They can color the public's understanding of science, motivate policy positions, ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In contrast to the idea of basic emotions, the circumplex model of affect proposes that human emotion is more complex and diverse than the basic emotion theory explains ( Russell, 1980 ). At least 28 interconnected emotional states of humans can be defined with two variables: emotional valence or sentiment and emotional arousal or intensity ( Citron et al , 2014 ; Freeman et al ., 2020 ; Yang & Chen, 2012 ). This two-dimensional model of human emotions defines emotional valence as positive and negative and emotional arousal as high and low ( Preoţiuc-Pietro et al , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the idea of basic emotions, the circumplex model of affect proposes that human emotion is more complex and diverse than the basic emotion theory explains ( Russell, 1980 ). At least 28 interconnected emotional states of humans can be defined with two variables: emotional valence or sentiment and emotional arousal or intensity ( Citron et al , 2014 ; Freeman et al ., 2020 ; Yang & Chen, 2012 ). This two-dimensional model of human emotions defines emotional valence as positive and negative and emotional arousal as high and low ( Preoţiuc-Pietro et al , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the majority of reactions observed across all posts and livestock species were positive (e.g., Likes and Loves). Freeman et al (2020) also reported that uncontroversial scientific findings shared on Facebook yielded a greater number of Likes than other reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of research on society is increasingly being considered by research communities (Samuel and Derrick, 2015;Bornmann, 2013;Shaikh and Alhoori, 2019). Additionally, a growing amount of scholarly content is shared and discussed on social media platforms on a daily basis (Ding et al, 2009;Fausto et al, 2012;Freeman et al, 2020Freeman et al, , 2019. The number of research articles shared on these platforms is estimated to be increasing at a rate of 5-10% per month (Adie and Roe, 2013).…”
Section: Online Impact Of Scholarly Articlesmentioning
confidence: 99%